Evaluation of Production Line Modelling in Qualified Cardboard Production with Reliability Analysis - Aykut Güleryüz; Mehmet Yılmaz; Hüseyin Ünözkan (Verimlilik Dergisi)
Purpose: To develop a new model for calculating the long-term production expectation of production lines and to show how this model can be used in production planning and control.Methodology: The methodology leverages real-world data to assess mechanical unit performance and improvement efforts. By calculating transition probabilities and employing Markov Chain and reliability analysis, it predicts long-term production capacity for the production line.Findings: It can predict long-term production expectations with high accuracy for a business with six production lines.Originality: The proposed model and method in this current study are capable of effectively addressing any production line problem where regular data is maintained.